Use of Only Oral Rehydration Salt Solution for Successful Management of a Young Infant with Serum Sodium of 201 mmol/L in an Urban Diarrhoeal Diseases Hospital, Bangladesh - Chisti, Mohammod J; Pietroni, Mark AC; Alom, Mohammad Samsul; Smith, Jonathan Harvey (Journal of Health, Population and Nutrition, 2012)
A boy aged 4 months 7 days was admitted to the Intensive Care Unit (ICU) of the Dhaka Hospital of icddr,b, Dhaka, Bangladesh, with the problems of acute watery diarrhoea with some dehydration, pneumonia, lethargy, and hypernatraemia (serum sodium of 201 mmol/L). Correction for hypernatraemia was tried by using only oral rehydration salt (ORS) solution. Seizures occurred during correction of the hypernatraemia.These were difficult to control and required three doses of injection lorazepam, a loading dose of injection phenobarbitone, followed by injection phenytoin and finally two doses of injection mannitol (even though there was no clinical or imaging evidence by ultrasonography or computed tomography of cerebral oedema). The correction was continued with ORS, and all the anticonvulsants were successfully weaned without any further seizures, and the patient recovered without any overt neurological sequelae.We present a case report of extreme hypernatraemia, which was successfully managed using only ORS. DOI: http://dx.doi.org/10.3329/jhpn.v30i3.12301 J HEALTH POPUL NUTR 2012 Sep;30(3):371-376